(3JGL GddZI hUMGM GdYQHjIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s ((3eOjfI aGS s)
(3ChdgG (B:s
(3ef HGH Gdeje aUd GdCdaG , bhdg hGdeCJe YfO GdYQH GdfSGA hjLJeYfi ai GdNjQ hGdTQ hGdLeY GdeBJe hYfO GdYGeI GdeUjHI s
(3GdLRA GdQGHY gh GdCNjQs
(3HgG fXGe GdJYbjHIs
(3JJab ai BNQgG ef BNQ fSNI YGQa MceJ (B28 (3dZI HGNJdGa jSjQ LOkG ai GdCdaGXs
(3fSNI SGHYI YTQI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GddZIs